Upregulation of ubiquitin conjugating enzyme E2B (Ube2b) ameliorates neuropathic pain by regulating Kcna2 (potassium voltage-gated channel subfamily A member 2) in primary afferent neurons. Issue 1 (1st January 2021) - Peng, Yuanzhi; Zhang, Qingqing; Cheng, Hao; Yan, Guizhen; Xing, Chunli
ABSTRACT: Neuropathic pain is a kind of pain caused by damage to somatosensory nervous system. Currently, neuropathic pain is still a medical problem for clinicians. Ubiquitin conjugating enzyme E2B (Ube2b) is validated to be implicated with nerve function, but whether Ube2b can play a role in neuropathic pain is still elusive. In this work, we constructed chronic constriction injury (CCI) rat model by ligating the left sciatic nerve, Ube2b protein expression was confirmed to be decreased in spinal cord tissues of CCI rats via Western blot analysis and immunofluorescence (IF) staining. Moreover, Ube2b elevation alleviated the thermal hyperalgesia and mechanical hyperalgesia in CCI rats according to paw withdrawal thermal latency (PWTL) and paw withdrawal mechanic threshold (PWMT). In addition, Hematoxylin-eosin staining revealed that Ube2b elevation suppressed chronic sciatic nerve injury. All these data suggested that Ube2b could ameliorate neuropathic pain in CCI rats. Mechanically, Ube2b upregulation elevated the protein level of Kcna2 (potassium voltage-gated channel subfamily A member 2) and decreased the protein level of DNMT3a (DNA methyltransferase 3 alpha). Ube2b elevation could increase Kcna2 expression via suppressing DNMT3a. Rescue assays unveiled that Ube2b overexpression modulated-mechanical hyperalgesia and thermal hyperalgesia were reversed by Kcna2 depletion, indicating that Ube2b alleviated neuropathic pain via mediating Kcna2 via the regulation of DNMT3a. In summary, we found that Ube2b elevation ameliorated neuropathic pain through regulating Kcna2, which might offer a novel biomarker for the therapies of neuropathic pain.